Family Meals and Disordered Eating in Adolescents: Are the Benefits the Same for Everyone? - Loth, Katie (Int J Eat Disord, 2014)
OBJECTIVE: To examine the association between family meals and disordered eating behaviors within a diverse sample of adolescents and further investigate whether family-level variables moderate this association. METHOD: Data from adolescents (EAT 2010: Eating and Activity in Teens) and their parents (Project F-EAT: Families and Eating and Activity among Teens) were collected in 2009–2010. Surveys were completed by 2,382 middle and high school students (53.2% girls, mean age = 14.4 years) from Minneapolis/St. Paul, MN, public schools. Parents/guardians (n = 2,792) completed surveys by mail or phone. RESULTS: Greater frequency of family meals was associated with decreased odds of engaging in unhealthy weight control behaviors in boys, and dieting, unhealthy and extreme weight control behaviors in girls. Results indicate that the protective effects of family meals are, in general, robust to family-level variables; 64 interactions were examined and only seven were statistically significant. For example, among girls, the protective nature of family meals against dieting and unhealthy weight control behaviors was diminished if they also reported family weight-related teasing (both p < .01). DISCUSSION: The results confirmed previous research indicating that participation in family meals is protective against disordered eating for youth, particularly girls. However, results suggest that in some cases, the protection offered by family meals may be modified by family-level variables.